LabVIEW Based Implementation of Resistive Temperature Detector Linearization Techniques - Ghaly, S. M. A. (Engineering, Technology & Applied Science Research, 2019)
Resistance temperature detectors (RTDs) are high-quality temperature sensors used for accurate temperature measurements and ideally suited for industrial applications, but their non-linearity is a serious drawback in temperature monitoring in which precise measurement and control are crucial. In this paper, two linearization techniques are implemented in LabVIEW environment involving voltage divider and feedback compensation circuits. The presented techniques considerably decrease the effects of non-linearity and may accommodate temperature variations).